2019
DOI: 10.1371/journal.pone.0212109
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of involvement of E-cadherin in cell fate specification or the segregation of Epi and PrE in mouse blastocysts

Abstract: During preimplantation mouse development stages, emerging pluripotent epiblast (Epi) and extraembryonic primitive endoderm (PrE) cells are first distributed in the blastocyst in a “salt-and-pepper” manner before they segregate into separate layers. As a result of segregation, PrE cells become localised on the surface of the inner cell mass (ICM), and the Epi is enclosed by the PrE on one side and by the trophectoderm on the other. During later development, a subpopulation of PrE cells migrates away from the IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 80 publications
2
19
0
Order By: Relevance
“…Thus, we expect the findings of our model to be translatable to the in vivo process of ICM formation. Taken together, our results, in agreement with the results of Filimonow et al and Yanagida et al indicate that the cells mechanical properties differentiate around E3.75 60,61 , allowing a cell sorting mechanism to act between E3.75 to E4.0. Our model points out that the observed cell fate clusters in 24 h old ICM organoids (reflecting E3.75 in the mouse embryo) do not require a cell sorting mechanism.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, we expect the findings of our model to be translatable to the in vivo process of ICM formation. Taken together, our results, in agreement with the results of Filimonow et al and Yanagida et al indicate that the cells mechanical properties differentiate around E3.75 60,61 , allowing a cell sorting mechanism to act between E3.75 to E4.0. Our model points out that the observed cell fate clusters in 24 h old ICM organoids (reflecting E3.75 in the mouse embryo) do not require a cell sorting mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…Even a modest difference in the expression level of a given cadherin is capable of leading to a cell sorting based on differential adhesion 59 . Filimonow et al showed that no difference in E-cadherin levels between Epi and PrE cells can be found until E3.75 60 . However, Yanagida et al showed that Epi and PrE cells are distinguishable by their expression of actin-cytoskeleton genes around E3.75–E4.5 61 , resulting in different mechanical properties of the cells and an increased motility of PrE cells compared to Epi cells 61 .…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies, primarily using mouse and rat models, have led to the understanding that E-cadherin and Ncadherin are required for the development of normal embryos, while P-cadherin appears not to be required for early embryogenesis (Kan et al, 2007;Radice et al, 1997). Formation of the trophectoderm epithelium is the first adhesion-dependent differentiation in the developing embryo and is influenced by E-cadherin (Fleming et al, 2001;Marrs & Nelson, 1996;Shehu, Marsicano, Flechon, & Galli, 1996;Watson & Barcroft, 2001), although Ecadherin may not be obligatory (Filimonow et al, 2019). Mouse embryos with mutated E-cadherin that lacked Ca 2+ binding had a disorganized morula shortly after compaction and failed to develop (Riethmacher, Brinkmann, & Birchmeier, 1995).…”
Section: Embryonic Developmentmentioning
confidence: 99%
“…Firstly, Bdh2 plays distinct roles in the regulation of primitive endoderm-like stem cell. It was reported that cellular adhesion of primitive endoderm (PrE) showed difference with epiblast (Stanton et al, 2019). Interestingly, we found downregulation of adhesion-related genes in Bdh2-knockout cells (Supplementary Figure 3D), which may explain the formation of smaller EBs in Bdh2-knockout ASCs/ESCs.…”
Section: Discussionmentioning
confidence: 58%